Eksplorasi Penggunaan Media Pembelajaran Big Book Dalam Mengenalkan Alat-Alat Optik Kepada Peserta Didik - Natasya; Wiwik Kurniyati; Femi Br Ginting; Afifa Suci Nahara; Oliver Chelsea Sitanggang; Desy Rosmalinda (Jurnal Lensa Pendas, 2025)
This research aims to explore the use of Big Book learning media in introducing optical tools to elementary school students. This study uses a qualitative approach with the type of library research. These sources are systematically analyzed to select, explore, evaluate, and synthesize the latest findings. The literature search is estimated to be published from 2020 to 2024. The source of the article searched or selected through an online search with the Google Scholar database uses the keywords "Big Book Learning Media" and "Optical Tools". Based on the results of the description of the literature study regarding the exploration of the use of big book learning media in introducing optical tools effectively increasing students' interest and understanding of the material. With its attractive visualizations and large size, the Big Book makes it easier to convey the concept of complex optical devices, such as microscopes, telescopes, and cameras, to be easier to understand. In addition, its use supports collaborative and interactive learning, thereby increasing the active involvement of students. Although there are several challenges, including limited availability of topics, limited interaction, strategies and integration of digital media and creative creation of Big Books can help optimize their use in learning. Thus, it is hoped that the Big Book can be a very useful tool in science learning, providing a more comprehensive and in-depth learning experience for students.